Risk Factors and Factors Related to Risk Behaviors Regarding to Hypertension and Diabetes Mellitus of People in Kamphaeng Phet Province - จารุวัฒน์ ลออศรี (Disease Control Journal, 2009)
The objectives were to stydy risk factors regarding to hypertension and diabetes mellitus, compared risk behaviors regarding to hypertension and diabetes mellitus between sex and age (35-39 years and equal or over 40 years) and to identify factors related to risk behaviors regarding to hypertension and diabetes mellitus among 864 people by interviewing datd from physical examination recording form. Data collecting was carried out during July - August, 2008. Descriptive statistics, t-test and multiple regression analysis were deployed for data analysing. The results indicated that 52.3 percent got moderate level of knowledge regarding to hypertension. 54.9 percent got moderate level of knowledge of diabetes mellitus. Risk factor regarding to hypertension was found that 37.3 percent had hereditary relatives got hypertension, and risk factor regarding to diabetes mellitus was found that 31.7 percent had overweight or fatty. Risk behaviors of hypertension between male and female, and between people at 35-39 years and equal or over 40 years, had statistical significant difference. Risk behaviors of diabetes mellitus between male and female had statistical significant difference, however, between people at 35-39 years and equal or over 40 years, had statistical non significant difference. Factor negatively related statistical significantly to risk behavior of hypertension was knowledge regarding to hypertension. Factors positively related statistical significantly to risk behavior of diabetes mellitus was education level (primary school or lower), and factors negatively related statistical significantly to risk behavior of diabetes mellitus was knowledge regarding to diabetes mellitus.